Programa inteligencia emocional para incrementar rendimiento académico en comunicación de 5º grado educación secundaria institución educativa “César Trelles Lara”, Piura - Garcia Marquez, Edy Ademir (2020)
ABSTRACT The purpose of this research was to determine the influence of the program on Emotional Intelligence in increasing academic performance in the area of Integrated Communication students 5th. Degree of Secondary Education I. E. "César Trelles Lara" of the city of Piura - 2018, this program was developed in a period of one academic semester, which ran through learning activities in a total of 16 sessions. The research was applied, taking a sample of 40 students (18 students in the control group and 22 students in the experimental group). Education Program Emotional Intelligence “Responsably for my emotions” as pre and post test a communication evaluation. The statistical probability of p = 0.000 is much lower than 0.05 (tc falls in the region of rejection of the null hypothesis, accepting the alternative hypothesis), it is determined that the application of Emotional Intelligence Program significantly influences the improvement in the Academic Performance Communication area, in the fifth grade students of secondary schools in the I.E. "César Trelles Lara" Piura – 2018.